Pelatihan Penggunaan Aplikasi Bandicam dan Quizziz dalam Pembelajaran bagi Guru-guru SDN Menteng Atas 14 - Shobah Shofariyani Iryanti; Muhammad Arifin Rahmanto (Publikasi Pendidikan, 2022)
School from home makes all learning activities carried out from home. However, the limited skills of teachers in using ICT-based learning media become an obstacle during online learning. Thus, training on the use of the Bandicam and Quizziz applications in learning for teachers of SDN Menteng Atas 14 is important to do during the Covid-19 pandemic. With this activity, it is hoped that teachers will be able to package interesting and fun learning. The method of implementing this community service activity is in the form of an online seminar. Seminar with the theme "Training on the Use of ICT-Based Learning Media (Bandicam and Quizziz)". held on Saturday, February 27, 2021 through the Zoom Cloud Meeting application with 25 participants. The first material discusses the development of learning media using the Bandicam application. The second material is about strategies for using interesting learning media. The third material is about the practice of using Quizziz in learning. This event runs smoothly and gives new enthusiasm for the participants in planning, designing, and implementing creative, inovative and fun learning so that students do not get bored easily in undergoing online learning so that learning objectives can be realized. The participants gave positive responses during the activity in the form of great enthusiasm in practicing the Bandicam and Quizziz learning media even though some participants were network constrained.